Atroposelective construction of biaryls enabled by a Ni(II)-catalyzed aerobic oxidation strategy - Pradhan, Chandini; Punji, Benudhar (ACS Central Science, 2025)
Enantioriched biaryls synthesis via aerobic oxidative cross-coupling of arenes involving <a class="ext-link" href="https://pubs.acs.org/doi/full/10.1021/acscentsci.4c01501" style="box-sizing: border-box; outline: none; text-decoration-line: none; color: rgb(51, 97, 184); transition: color 0.3s; font-family: Roboto, arial, sans-serif; font-size: 16px;">bioinspired oxygen activation by Ni(II).